Analisis Pengaruh Experiential Marketing terhadap Loyalitas Pelanggan Hotel "X" Semarang - Putri, Yuwandha Anggia; Astuti, Sri Rahayu Tri (Jurnal Ilmiah Aset, 2010)
The objective of this research was to find out: a. how big the influence of sense, feel, think, and relate partially toward customer loyalty of hotel â€œXâ€ Semarang; b. how big the influence of sense, feel, think, act, and relate simultaneously toward customer loyalty of hotel â€œXâ€ Semarang. The samples of this research were 100 customers that were staying or had stayed in the hotel â€œXâ€ Semarang. The sampling technique was accidental sampling. The analysis technique was quantitative, with multiple linear regression, t test, and F test. The result by using program of SPSS indicated that sense, feel, think, act, and relate had positive influence to customer loyalty. The result of partial hypothesis showed that sense, feel, think, act, and relate had positive significant influence with significance level less than 0.05. So, it can be concluded the formula hypothesis was correctly proven. The result of simultaneous hypothesis showed that variable of sense, feel, think, act, and relate had positive significant influence with significance level F less than 0.05, so Ho was refused and Ha was accepted. It means that the hypothesis which stated â€œthere was positive and significant influence of sense, feel, think, act, and relate to customer loyalty (Y)â€ was truly proven.